A novel method to prevent recurrent balloon rupture during dilation of heavily calcified conduits in preparation for transcatheter pulmonary valve placement. Issue 3 (26th August 2015) - Abu Hazeem, Anas; Aldoss, Osamah; Fagan, Thomas
Abstract : Introduction: A 24‐year‐old female presented for percutaneous pulmonary valve placement. She was born with tetralogy of Fallot and had initial palliation with a Blalock–Taussig shunt followed by complete repair at age of 4 years including placement of a homograft conduit in the right ventricle to pulmonary artery position. She had developed severe obstruction in the conduit. Procedure: Angiography showed a heavily calcified conduit with moderate insufficiency. During pre‐dilation, a total of six balloons ruptured due to heavy conduit calcification prior to reaching desired inflation diameter. Subsequently, double balloon technique was attempted using two 9‐mm Conquest balloons. One of the conquest balloons was then replaced by 16‐mm Atlas balloon and conduit dilation was performed. At full inflation, the Conquest balloon ruptured. The deflated ruptured Conquest balloon was kept in the conduit and the Atlas balloon was exchanged for 18 and then 20‐mm Atlas balloons and both were used to dilate the conduit. The deflated ruptured Conquest balloon protected the Atlas balloons and conduit angioplasty proceeded successfully without further rupture of any balloon. Subsequently, four stents were placed in the conduit followed by delivery of Melody Valve using a 20‐mm Ensemble system with excellent results. Conclusion: This case illustrates a novel method of using the body of a ruptured balloon to protect subsequent balloons from rupture due to heavy conduit calcification. This method requires the presence of two venous access lines but might save time, effort, and cost from repeated balloon ruptures. © 2015 Wiley Periodicals, Inc.